Assessing the effects of Celebrity Endorsements of Political Parties: An empirical study of Nigerian 2019 Presidential Elections - Abdurrahaman, Daha Tijjani; Owusu, Acheampong; Bakare, Akeem Soladoye; Apejoye, Adeyanju; Ibrahim, Muhammad Muhsin; Ahmad, Tijjani Habibu (Technium Social Sciences Journal, 2021)
This research aims to examine the impact of celebrity endorsement on Political Parties and its influence on electorates to vote for a particular Party’s candidate. The mediating role of Political Brand Credibility (PBC) and Political Brand Equity (PBE) towards Voting Intention (VI) relationships were also examined. The study’s conceptual framework was developed using The Source Credibility, The Associative Network Memory Model, and the Brand Signalling Theory. Primary survey data was collected online and analysed through Structural Equation Modelling. Findings suggest that Endorser Credibility has a direct positive significant relationship with Political Brand Credibility. However, there is no significant direct correlation between Endorser Credibility and Political Brand Equity and Voting Intention. Nevertheless, indirect relationship was established. Findings from the study has proven that the endorsement of celebrities alone does not necessarily influence electorates to vote for political candidates, rather the Credibility of the Party and its Equity play a pivotal role with regards to the Voting Intention of voters. Practically, this study has given us insights into the endorsement of celebrities of political candidates, which the Political Party leaders should consider before bringing on board any celebrity to endorse their candidates. Future research opportunity and limitations were also discussed.